Questioning the Ideal Number of Visitors at the Mangrove Track in Budo Village, North Sulawesi, Indonesia - Sangari, Fonny; Pearl Loesye Wenas; Frans Victor Rattu; Dimas Ero Permana; Jeanlly Adri Solang; Jufrina Mandulangi (Faculty of Economics and Business, University of Mataram, 2024)
Since the Indonesian government's policy, rural tourism development has been prioritized. Many villages are trying to develop their villages into tourist villages. Especially with the best tourist village award, the impact is that all villages compete to get the award. Budo Village is a tourist village located in North Minahasa Regency, North Sulawesi Province, Indonesia. This village went viral because it received the award for the 50 Best Tourism Villages in Indonesia 2022. Since it was first opened, many visitors have come to the location. The average number of visitors in one day can reach 1500 people, it is mentioned that almost between visitors cannot pass each other while walking on the mangrove track. This is because there is no limit to the number of visitors in the area. The purpose of this study is to assess the ideal number of visitors at the track, for the sustainability of the tourist site, and to preserve the tourist environment. The method used in this measurement is the Carrying Capacity of the Area. The results of this study will recommend to the tourism manager how to manage the number of visitors that will have an impact on the sustainability of the tourist attraction.